PENGARUH KEPEMIMPINAN KEPALA MADRASAH DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MADRASAH - Putri Melati; Jumira Warlizasusi; Muhammad Istan (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2022)
This study examined and evaluated the influence of the principal's leadership on teachers’ performance, the impact of the work environment on teachers’ performance, and the combined impact of leadership and the work environment. This study collected primary data from 391 teachers as a sample representing all teachers from 297 madrasahs in Bengkulu using a questionnaire. Fcount = 30.850, Probability (sig) = 0.000 = 0.05, indicating that two independent factors, namely leadership (X1) and work environment (X2) had a positive and statistically significant effect on teachers’ performance (Y). Meanwhile, the contribution of the two independent variables namely leadership (X1) and work environment (X2) to teachers’ performance was quite large, as evidenced by the determination index value (R2) of 0.615 or the variance of teacher performance of 61.50%. Other factors not included in this study determined 0.361 or 36.10% of teachers’ performance.